Simulation of Uranium and Plutonium Oxides Compounds Obtained in Plasma; AIP Conference Proceedings; Vol. 1938 : Isotopes: Technologies, Materials and Application (ITMA-2017) - Novoselov I. Yu. Ivan Yurievich (2018, 2018)
Title screen